A graduate’s employability study of bachelor of science in entrepreneurship of Isabela State University, Philippines - Ma Teresa Silos Alvarez; Eva Uminga Cammayo (Institute of Advanced Engineering and Science, 2023)
The bachelor of science in entrepreneurship (BSE) program is offered to address the needs of learners who want to obtain a degree adapted to their talents and abilities to contribute to the industrialization of the country. To assess transparency, the college has the responsibility to keep track of the success of its graduates and whether their curriculum has affected the person, the society, or the country. The graduate tracer analysis will aid in evaluating the employability of the graduate and define the multiple variables that will act as a framework for optimizing students’ college instruction and facilities. In this tracer study, 69 alumni who graduated from 2013 to 2017 were surveyed using a modified graduate tracer study (GTS) instrument, administered using social media and other digital platforms. The contribution to alumni employability of factors: curriculum, student services, facilities, faculty competence, methods of instruction, and career guidance-were quantified and ranked. Based on the results, the most significant factors contributing to alumni employability were course content/curriculum, student services (training, seminars), and facilities. As such, the researchers recommend strengthening the BSE curriculum, conducting employee training and seminars, and streamlining administrative facilities.